PENGAWASAN PERBANKAN SEBAGAI BENTUK PERLINDUNGAN HUKUM BAGI NASABAH BANK - Aniek Tyaswati Wijilestari (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2021)
Bank is a business entity that collects funds from the public in the form of deposits and distributes them to the public in the form of credit or other forms. Bank activities carry a very high risk because they are dealing with a very large amount of money, which can lead to the intention of the parties involved to commit fraud. Therefore, in exercising control, it is necessary to create a layered system to anticipate and protect the bank's customers. Effective and good supervision is a preventive step in stemming, or at least reducing cases of customer loss with bank actions. The enactment of Law Number 21 of 2011 concerning the Financial Services Authority which was promulgated on November 22, 2011, led to a change in the duties and authority of regulation and supervision in the banking sector which was previously transferred by Bank Indonesia to the Financial Services Authority, so that an assessment of financial conditions and conditions banking institutions as a whole are under the Financial Services Authority. The supervision of the Financial Services Authority is aimed at ensuring that each individual bank is healthy and safe, and the entire banking industry is healthy, so as to maintain public trust which leads to legal protection for bank customers.